UTICAJ FAKTORA ZA KREIRANJE VREDNOSTI I KONKURENTSKE PREDNOSTI ORGANIZACIJE NA LJUDSKI KAPITAL U ORGANIZACIJI - Brzaković, Stefan; Brzaković, Aleksandar; Đurđević, Sanja (Journal of process management and new technologies, 2023)
Abstract: The significance of human capital management strategies in acquiring and maintaining advantages against the competition is determined by extensive academic studies. Research studies show that competitive advantage on the market can be maintained through a systematic attraction, development, motivation, management and appreciation of human resources in an organization. In order to maintain their competitive advantage(s) and ensure their survival, organizations have to take care of the strategy of scale, the diversification of activities, the allocation of resources, the orientation towards the buyer, value chains, change management, innovations and the strategic renewal of the organization itself. Organizations that manage human resources can freely be said to be making better financial results if perceived through different parameters, such as revenue growth, productivity, the volume of sales, the operational profit, the net profit margin, return on capital, share value growth, i.e. the growth of the market value of the organization. This paper is aimed at determining whether the level of the factors for creating the value of the organization and the level of the competitive advantage of the organization actually affect or do not affect the level of human capital in the organization. Based on the research conducted in the paper, it can be concluded that the level of human capital in the organization increases simultaneously with the increasing of the level of the factors for creating the value of the organization and the level of the competitive advantage of the organization.